Dampak Berita Emas Palsu Terhadap Harga Saham PT Aneka Tambang TBK (ANTM): Analisis dan Prediksi) - Ispaniyah, Ispaniyah; Tyas, Putri Cahyaning; Suseno, Akrim Teguh; Wulandari, Umi Meganinditya (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2025)
Fake news or hoaxes, have become a major problem around the world in recent years. This phenomenon not only affects public opinion but can also affect various aspects of socio-economic life, including financial markets. Currently, global stock prices continue to rise and have reached their highest level since 2012-2013. One of the leading mining companies in Indonesia, PT Aneka Tambang Tbk (ANTM), is not entirely dependent on its share price. The impact of fake news on stock prices has become a topic of growing interest in the academic literature. Various previous studies have attempted to identify the relationship between the spread of fake news and stock price fluctuations. Using the RapidMiner application, an analysis of PT ANTM's stock price prediction was conducted using Neural Network (NN) and Linear Regression (LR) algorithms. To assess the accuracy of the prediction, the analysis is performed using the Root Mean Square Error (RMSE) results. The comparative analysis conducted shows that the Neural Network algorithm has a lower error rate of 14,806 +/- 0.000 compared to the Linear Regression algorithm which has a value of 22,379 +/- 0.000. This shows that the Neural Network algorithm has higher accuracy in predicting the share price of PT ANTM. A smaller RMSE value indicates a more accurate prediction. In addition, this study also identified that the time span of the data used (December 19, 2023 - June 19, 2024) can affect the prediction results. Based on the conclusions, the researcher suggests that using a dataset with a longer time span and applying other Deep Learning algorithms to improve prediction accuracy can be used for future research.